Optična pinceta in ustvarjanje ultrakratkih optičnih sunkov visokih intenzitet, Nobelova nagrada za fiziko 2018 - Osterman, Natan (Obzornik za matematiko in fiziko, 2018)
Artur Ashk n, Gerard Mourou and Donna Strickland were awarded the 2018 Nobel Prize in Physics for their groundbreaking inventions in laser physics. A historical pathway to the modem optical tweezers, its operation and use in research are outlined in the first part o f the article, whe reas in the second part we describe the chirped pulse amplication technique for creation of high-intensity, ultra-short optical pulses, a.5 well as the use and current reoords of modern pulsed laser systems.
Keywords: eksperimentalna postavitev; optična pinceta; tehnika CPA; ultrakratki laserski sunki